2023
DOI: 10.1021/acs.jmedchem.2c01714
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Bipyridazine Derivatives as Stimulator of Interferon Genes (STING) Receptor Agonists

Abstract: The development of stimulator of interferon genes (STING) agonists has been of potential applications for the treatment of cancer and infectious diseases. Based on the crystal structure of SR-717 bound to hSTING, we designed and synthesized a novel series of bipyridazine derivatives as highly potent STING agonists. Among them, compound 12L led to significant thermal stability shifts of the common alleles of hSTING, as well as that of mSTING. 12L also displayed potent activities in various hSTING alleles and mS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…Among these compounds, 12J, 12K, and 12L had the lowest ΔΔG bind values of less than −0.6 kcal/mol (Figure 7B and Table S5), suggesting that the substitution of the fluorine might influence agonist binding. In the previous competition binding assays, 12J, 12K, and 12L showed higher binding affinities with IC 50 values of 1.89, 1.75, and 1.15 μM, compared with SR-717 (IC 50 = 9.81 μM), 35 highly consistent with our calculations. According to the binding models of these agonists to STING (Figure 7C), β4 and α5 interacted with the aromatic ring and the halogens (or alkynyl group), respectively.…”
Section: ■ Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among these compounds, 12J, 12K, and 12L had the lowest ΔΔG bind values of less than −0.6 kcal/mol (Figure 7B and Table S5), suggesting that the substitution of the fluorine might influence agonist binding. In the previous competition binding assays, 12J, 12K, and 12L showed higher binding affinities with IC 50 values of 1.89, 1.75, and 1.15 μM, compared with SR-717 (IC 50 = 9.81 μM), 35 highly consistent with our calculations. According to the binding models of these agonists to STING (Figure 7C), β4 and α5 interacted with the aromatic ring and the halogens (or alkynyl group), respectively.…”
Section: ■ Introductionsupporting
confidence: 91%
“…Integrating with our MD simulation results, we conducted free-energy perturbation (FEP) calculations to decipher the structure−function relationship of seven STING agonists. 35 Compared with the ligand-binding free energy of SR-717 to STING, the relative energies (ΔΔG bind ) of seven agonists were calculated (Figure 7, S9−S11 and Tables S4−S5). All of these agonists had a functional group different from the imidazole group of SR-717.…”
Section: ■ Introductionmentioning
confidence: 99%
“…SR-717 served as a direct cGAMP mimetic, wherein two molecules of SR-717 induced the same closed STING conformation and exhibited a preferable affinity as well as systemic antitumor efficacy . Currently, a series of SR-717 derivatives bearing a bipyridazine framework were designed and synthesized, which possessed the activating potency on STING and favorable PK properties, as well as good antitumor effect . The benzothiazinone STING agonist G10 was disclosed by VGTI and was obtained through high-throughput screening (HTS).…”
Section: Introductionmentioning
confidence: 99%
“…33 Currently, a series of SR-717 derivatives bearing a bipyridazine framework were designed and synthesized, which possessed the activating potency on STING and favorable PK properties, as well as good antitumor effect. 34 The benzothiazinone STING agonist G10 was disclosed by VGTI and was obtained through high-throughput screening (HTS). Further structural modification and optimization of the benzothiazinone moiety rendered the indole compound C53 bound to a new site on the STING transmembrane domain, which mediated the oligomerization of STING dimer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…22 Recently, we reported a series of bipyridazine derivatives as STING receptor agonists. 23 In the optimal procedure of the structures, we found that compound 4A (Figure 2), which contains a 1H-pyrrole-3-carbonitrile core structure, increased the thermal stability of hSTING REF with a ΔT m value of +3.5 °C and robustly induced reporter signal in THP1 cells with an EC 50 value of 10.49 ± 1.95 μM (Figure 2). Hence, compound 4A represents a promising lead compound for further design and optimization.…”
mentioning
confidence: 99%